JUSTIFICATION OF OPTIMAL LOCATION OF CONNECTION OF THE DISTRIBUTED GENERATION SOURCE AND VALUE OF ITS POWER - V. V. Kyryk (National Technical University "Kharkiv Polytechnic Institute", 2019)
Goal. To analyze the options for the development of the 110 kV electricity network with sources of distributed generation. Establishing the relationship between power of the source of distributed generation with the voltage changes in the nodes and transformer active power losses change. To provide the minimum value of network active power loss the authors justify the conditions for optimal connection of the source of distributed generation and value of its power. Methodology. The authors have used the DigSilent Power Factory software environment to create a 110 kV network model and have made a series of simulation of the network operating modes with solar power plants. Results. Based on the operational parameters it is established that the change in power generation in the accepted limits normally does not lead to abnormal voltage variations in the nodes, with power losses having characteristic changes due to alterations in the network of power flows. In the network with solar power plants, the transformer losses of active power is reduced with increasing generation power, except for the most remote nodes from the balancing point, in which losses reduction takes place with load of transformers approximately up to 60 %. At significant overloads of transformers (up to 130 %) there is reactive power losses increasing in comparison with losses in the network without solar power plants. The dependence of active power losses in the network on the load of transformers has a nonlinear character). For each node at one value of transformer load the active losses are different. Less reactive power losses occur at lower load ratios of transformer. When increasing the load of transformers, the rate of increase in reactive losses is higher than the active ones. Also for closed networks with voltage of 110 kV it has been found that the optimal node for connecting the distributed generation is a node with a flow division of power. If there are several such nodes in the network, the optimal one for connecting is the node with the maximum load. The optimal power of the solar station in the node should not exceed 110 % of the installed transformer's power. Originality. For the first time the dependence between the place of the best connection source of the distributed generation with the point of flow distribution with the greatest current fraction from network balancing point was established. In this case the power of the source of distributed generation must not exceed 10 % of the total power of the transformers in this node. Practical significance. We have obtained reasonable conditions for connecting source of distributed generation to a closed electric network of 110 kV without performing large volumes of mode calculations. Namely, the optimal connection point is the point of flow distribution with the greatest current fraction from network balancing point.